Biosynthetic study of conidiation-inducing factor conidiogenone: heterologous production and cyclization mechanism of a key bifunctional diterpene synthase. Issue 2 (1st February 2019) - Shiina, Tetsuya; Nakagawa, Kazuya; Fujisaki, Yukiko; Ozaki, Taro; Liu, Chengwei; Toyomasu, Tomonobu; Hashimoto, Masaru; Koshino, Hiroyuki; Minami, Atsushi; Kawaide, Hiroshi; Oikawa, Hideaki
ABSTRACT: Conidiogenone, a diterpene with a unique structure, is known to induce the conidiation of Penicillium cyclopium . The biosynthetic pathway of (−)-conidiogenone has been fully elucidated by the heterologous expression of biosynthetic genes in Aspergillus oryzae and by in vitro enzyme assay with 13 C-labeled substrates. After construction of deoxyconidiogenol by the action of bifunctional terpene synthase, one cytochrome P450 catalyzes two rounds of oxidation to furnish conidiogenone. Notably, similar biosynthetic genes are conserved among more than 10 Penicillium sp., suggesting that conidiogenone is a common conidiation inducer in this genus. The cyclization mechanism catalyzed by terpene synthase, which involves successive 1, 2-alkyl shifts, was fully elucidated using 13 C-labeled geranylgeranyl pyrophosphate (GGPP) as substrate. During the structural analysis of deoxyconidiogenol, we observed broadening of some of the 13 C signals measured at room temperature, which has not been observed with other structurally related compounds. Careful examination using techniques including 13 C NMR studies at −80 °C, conformational analysis and prediction of the 13 C chemical shifts using density functional theory gave insights into this intriguing phenomenon. Graphical abstract: : Heterologous expression of bifunctional diterpene synthase and P450 monooxygenase genes from two Penicillium sp. afforded conidation inducing factor conidiogenone.